THE DETERMINANT OF WEBSITE QUALITY AND E- SERVICE QUALITY AT SME IN INDONESIA - Tatik Suryani; Abu Amar Fauzi; Moch Nurhadi (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2020)
This study aims to examine the dimensions which determine the Website Quality and E-Service Quality in Small and Medium Enterprises (SMEs) in Indonesia. As one of the important determinant dimensions for website quality, E-Service Quality is specifically observed to find out the specific factors that determine E-Service quality which in some previous studies has not been widely studied. The study was conducted by using survey method with questionnaire involving 379 SME customer respondents. Website quality dimensions are measured using a Likert Scale with 5 alternative answers. The results of the analysis conducted with Smart PLS, shows that there are four dimensions of website quality determinants, of which the most influential are: E-Service Quality, Information Quality, System Quality and Image Quality; furthermore for E-Service Quality dimensions, there are three identified important dimensions that determine are: Fulfillment, Responsiveness, and System Availability